International strategies in fighting against medicaments fraud and other similar offences: the MEDICRIME Convention - Romeo Casabona, Carlos M. (Crime, law and social change, 2017)
The Council of Europe has passed a convention which constitutes, for the first time in world history, a binding international treaty in the criminal law field "On counterfeiting of medical products and similar crimes involving threats to public health" (MEDICRIME Convention). Safeguarding of public health through penal measures against criminal behaviours, protection of victims, promotion of cooperation at national and international levels and preventive measures are the overarching aims of the above convention. Counterfeiting medical products and similar crimes threaten the right to life enshrined in the European Convention on Human Rights and Fundamental Freedoms (thereafter ECHR). Incidences of counterfeit medical products and similar crimes undermine public trust in healthcare systems and authorities’ surveillance thereof. Counterfeiting of medical products and similar crimes have a global spread, no country is spared. The present paper brings to light the added value of the MEDICRIME Convention in order to protect public health at the international level and analyses the substantive criminal law aspects of the Convention.